2019
DOI: 10.3390/w11020203
|View full text |Cite
|
Sign up to set email alerts
|

Halloysite Nanotubes as Adsorptive Material for Phosphate Removal from Aqueous Solution

Abstract: In this study, we were aiming at testing halloysite nanotubes as an efficient adsorbent for the removal of phosphate from agricultural runoff. Adsorption of phosphate onto powder and granular form of halloysite nanotubes has been examined by using the classical batch method and diffusion experiments at room temperature. Different forms of halloysite nanotubes were investigated to explore the effect of structure on the adsorption of phosphate. The maximum adsorption efficiency was obtained for powder halloysite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…To understand the sorption mechanism in the nitrate sorption process, the experimental data were fitted with three common kinetic models, namely pseudo-first-order equation (equation (2)), pseudo-second-order equation (equation (3)) and intraparticle diffusion equation (equation (4)) (Fu et al., 2015; Saki et al., 2019) where Q e and Q t are the sorption amount (mg/g) at equilibrium and at time t (min), respectively; C (mg/g) is a constant; while k 1 (1/min), k 2 (g/mg/min) and k ipd (mg/g/min 0.5 ) are the rate constants for the pseudo-first-order, pseudo-second-order and intra-particle diffusion equations, respectively. The correlation parameters and coefficients ( R 2 ) are listed in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the sorption mechanism in the nitrate sorption process, the experimental data were fitted with three common kinetic models, namely pseudo-first-order equation (equation (2)), pseudo-second-order equation (equation (3)) and intraparticle diffusion equation (equation (4)) (Fu et al., 2015; Saki et al., 2019) where Q e and Q t are the sorption amount (mg/g) at equilibrium and at time t (min), respectively; C (mg/g) is a constant; while k 1 (1/min), k 2 (g/mg/min) and k ipd (mg/g/min 0.5 ) are the rate constants for the pseudo-first-order, pseudo-second-order and intra-particle diffusion equations, respectively. The correlation parameters and coefficients ( R 2 ) are listed in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum amount of nitrate adsorbed onto SE-1 was found higher than that on A 520E when the sorption equilibrium reached. To understand the sorption mechanism in the nitrate sorption process, the experimental data were fitted with three common kinetic models, namely pseudo-first-order equation (equation 2), pseudo-second-order equation (equation 3) and intraparticle diffusion equation (equation 4) (Fu et al, 2015;Saki et al, 2019) Q t ¼ Q e ð1 À e Àk 1 t Þ…”
Section: Characterization Of Se-1 Resinmentioning
confidence: 99%
“…Finally, a larger h0 value of AEE-3 was obtained, and the difference in the adsorption rate is related to the difference of the resin matrix. Figure 3 describes the effect of contact time on NO 3 − -N uptake by AEE-3 and A520E at 298 K, and all the data were simulated using two commonly used kinetic models [21,22]:…”
Section: Adsorption Kineticsmentioning
confidence: 99%
“…describes the effect of contact time on NO3 − -N uptake by AEE-3 and A520E at 298 K, and all the data were simulated using two commonly used kinetic models[21,22]:Pseudo-first-order:…”
mentioning
confidence: 99%
“…Whilst kaolinite has been studied regularly for its phosphate adsorption properties (Edzwald et al , 1976; He et al , 1997; Gimsing & Borggaard, 2002; Kamiyango et al , 2009; Gérard, 2016), there is surprisingly little published work on halloysite (7 Å). Very recent work that has investigated halloysite has found adsorption capacities of 1.5 mg g –1 for phosphate after 3 h equilibrium time (Almasri et al , 2019), whilst Saki et al (2019) reported that granular halloysite adsorbs more phosphate than powdered halloysite due to the availability of pore space, with a maximum adsorption of ~1.2 mg g –1 phosphate.…”
mentioning
confidence: 99%